2011
DOI: 10.1016/j.bcp.2011.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of ellagic acid, a natural polyphenolic compound, in a murine model of Crohn's disease

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.Page 1 of 37A c c e p t e d M a n u s c r i p t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(104 citation statements)
references
References 46 publications
(49 reference statements)
7
96
0
1
Order By: Relevance
“…It is well accepted that the NF-κB pathway plays an important role in the maturation of UC ( Wong and Tergaonkar, 2009 ) and the inflammation process, and has been developed as a target for seeking anti-inflammatory agents from natural products. For example, ellagic acid and curcumin, which are naturally occurring plant phenols, exhibited anti-inflammatory activity through NF-κB signaling pathway by preventing I κB degradation and inducing an inhibition of the nuclear translocation of p65 ( Kim et al, 2005;Rosillo et al, 2011 ). In THP-1 cells, MQEO (v/v, 0.01 ‰ −0.05 ‰ ) effectively prevented the LPS-stimulated increase in TLR4 expression and markedly blocked the downstream I κB kinase (IKK) and I κB phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…It is well accepted that the NF-κB pathway plays an important role in the maturation of UC ( Wong and Tergaonkar, 2009 ) and the inflammation process, and has been developed as a target for seeking anti-inflammatory agents from natural products. For example, ellagic acid and curcumin, which are naturally occurring plant phenols, exhibited anti-inflammatory activity through NF-κB signaling pathway by preventing I κB degradation and inducing an inhibition of the nuclear translocation of p65 ( Kim et al, 2005;Rosillo et al, 2011 ). In THP-1 cells, MQEO (v/v, 0.01 ‰ −0.05 ‰ ) effectively prevented the LPS-stimulated increase in TLR4 expression and markedly blocked the downstream I κB kinase (IKK) and I κB phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…The kidneys were removed and washed with ice-cold 0.9 % NaCl. The dose and administration period have been selected corresponding to the previous studies (Rosillo et al 2011;Shi et al 2008;Zhou et al 2008).…”
Section: Animals Experimental Designmentioning
confidence: 99%
“…EA decreased COX-2 and iNOS protein expressions induced by TNBS. EA also inhibited both MAPK (ERK, JNK, and p38) pathways by preventing their phosphorylation and NF-κB pathway by preventing the IκBα degradation and the nuclear translocation of p65 in the intestinal epithelial cells from inflamed rat colon (Rosillo et al, 2011).…”
Section: Rat Studiesmentioning
confidence: 93%
“…Among the in vivo studies on the effects of pomegranate PCs on intestinal inflammation related to IBDs, four studies conducted on murine models were reported in the literature: three with rats (Larrosa et al, 2010;Ogawa et al, 2002;Rosillo et al, 2011) and one with mice (Singh et al, 2009). Experimental models of IBD were induced by a daily oral administration of dextran sulphate sodium (DSS) at 2-5% (v/v) in drinking water or by intra-colonic administration of trinitrobenzene sulfonic acid (TNBS).…”
Section: In Vivo Intestinal Anti-inflammatory Effects Of Pomegranate mentioning
confidence: 99%